Apoptosis in lichen sclerosis of the vulva in menopausal women - Rotsztejn, Helena; Jesionek-Kupnicka, Dorota; Zalewska, Anna; Łukaszek, Stanisław (Menopause Review/Przegląd Menopauzalny, 2005)
Apoptosis is a physiological process regulating homeostasis in the organism. Hyperkeratosis in the skin is regarded as a programmed cell death. The aim of the study was to evaluate apoptosis in lichen sclerosis of the vulva. ApoTag (Boehringer-Manheim, Germany) was employed in the study. It was demonstrated that in early lesions apoptotic cells accounted to 5,4 cell per 100 of epithelial cells, whereas in older lesions apoptosis was close to 0. Apoptosis was not observed in lymphocytic infiltrations. In the control group apoptosis was found in 1 per 100 epithelial cells. The obtained results indicate distorted apoptotic processes in lichen sclerosus.